Factors that Lead to the Supply Chain Safety Compliance in Air Cargo Industry - Siti Fairuza Hassam; Nurdiyana Nazihah Zainal; Jamaludin Akbar; Mohd Rizaimy Shaharudin; Nurul Ain Kamalrudin (International Journal of Supply Chain Management, 2018)
This study aims to determine the factors that lead to the supply chain safety compliance in Air Cargo in Malaysia. By using the purposive sampling technique, the questionnaires were distributed to the selected respondents for the gathering of data and analysis purposes. It was found that, organisational commitment, employee involvement, and safety training factors have a positive significant influence towards supply chain safety compliance evaluation. Moreover, the safety training factor showed the most significant influence as compared to the others. However, the study found the insignificant relationships between personal protective equipment (PPE) factor with supply chain safety compliance in workplace practices. Workers were lacked awareness on how to comply with safety regulations, especially when it came to wearing safety equipment while handling the movement of material in supply chain processes. This will be a main concern of industry, especially for the Air Cargo Industry, to take more proactive steps in tackling the safety compliance issues occurrences and in achieving the Occupational Safety and Health (OSH) best practices in supply chain activities related.